Diabetes mellitus related complications in out- patient clinic of tertiary care hospital - Maskey, R; Shakya, DR; Sharma, SK; Karki, P; Lavaju, P (Journal of College of Medical Sciences-Nepal, 2012)
We tried to explore the demographic profile and complications of the out patients suffering with Diabetes Mellitus (DM). It was hospital based descriptive study conducted among the 100 diabetic out-patients of B.P.Koirala Institute of Health Sciences, Dharan, Nepal during the period of 1-1-2010 to 29-2-2010. Patients above 14 years diagnosed as per ADA guidelines 2009 giving written informed consent were taken. The number of common diabetes related complications were searched and diagnosed clinically with the use of relevant investigations which included macro-vascular complications like ischemic heart disease, peripheral vascular disease, and micro-vascular complications like diabetic retinopathy, diabetic neuropathy, and diabetic nephropathy. Among 100 confirmed cases of diabetes mellitus (51 male and 49 female).Of all diabetes, 99% were type 2, 1% were type1. About 42% subjects were of age group between 40-60 yr. When BMI?23 kg/m2 (as recommended for Asians) is taken as the determining factor for overweight, 29% of patients were overweight, 56% obese and 6% morbid obese. About 83% of subjects were on OHA, 9% on Insulin and 8% on OHA and insulin both. The most common and frequent chronic complications were neuropathy (44.4%) followed by cardiovascular and retinopathy (27.7%), nephropathy (16.6%) and others (11.3%). About 25 % of subjects had hypertension (stage 1 hypertension-17%, and stage 2 hypertension 8%).As most of the patients are overweight with more neurological and cardiovascular complications so the lifestyle changes are required with regular antidiabetics and dietary restriction. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 9-16 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6674